THE STUDENTS’ PERCEPTION OF USING EXTENSIVE READING MATERIAL BASED ON CEFR FRAMEWORK - Fithriani, Luthfia; Paradisca, Methy Lina; Sugiarto, Intan Choirunisa; Drajati, Nur Arifah (Universitas Muhammadiyah Palembang, 2020)
Extensive Reading is an activity to read a text-based on someone's interest, and it is an effective method to improve reading skills. Nowadays, the university promotes Extensive Reading to boost students’ interest in reading along with improving reading skills. The purpose of this research is to investigate the students’ perception of using material Extensive Reading based on the CEFR Framework. This research using the qualitative method and collecting the data through SHOWeD. The participants in this research were 14 EFL college students of University in Indonesia who are following the Extensive Reading class for 16 meetings in 4 months. The result finds out that the students have positive perceptions toward Extensive Reading based on CEFR as material in reading.